Влияние анемии на формирования болезни почек у детей в республике Каракалпакстан - Жиемуратова, Гулпаршын Кошкинбаевна; Аяпбергенова, Юлдузхан Ембергеновна; Айтмуратова, Урхия Каллибековна (Медицина: теория и практика, 2020)